Development of Ontology Models on Vitamin Suplements Domain - I Made Dirga Adi Guna; I Ketut Gede Suhartana (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
The amount of vitamin suplements that sold in the world today causes people have more option to consider when choosing the right vitamin suplements to maintain their health and fulfill their nutritional adequacy rate. The number of vitamin suplements product available with various types and criteria requires consuments to be more careful when choosing the right vitamin suplements for their body. The right solution to overcome this problem is to use ontology models. The ontology method used in this research is Methontology. This method is one of the most popular method of building an ontology model that can be used as a reference for further research. The development of ontology models in this research use an app called Protégé 5.5.0. and in the evaluation process, ontology gives great result on answering the questions that given by users.